Digital Instructions and Self-Directed Learning as Determinants of Academic Performance Amongst Higher Education Institutions’ Students (Heis) - Eluemuno, Azukaego Ifeoma; Nwikpo, Mary Nneka; Ipem, Josephine Nkechinyere (Asosiasi Asesmen Pendidikan (AAP), 2025)
The rapid digitalization of education has transformed instructional methodologies in higher education institutions (HEIs). This paper explores the role of digital instruction and self-directed learning (SDL) as key determinants of academic performance. While digital instruction offers flexibility and accessibility, SDL empowers students to take ownership of their learning. The interplay between these factors significantly influences academic success. The population of study covered all the students of the government owned tertiary institutions in the six geopolitical zones used for the study. The study adopted the correlational survey design and utilized purposive sampling technique to select 185 students from the institutions. The instruments used for the study was developed by the researchers, titled Digital Instructions and Self-directed Learning as determinants of academic performance amongst Higher Education Institutions’ Students (HEIs) Questionnaire (DIaSLdAHEIsQ). The instrument was validated by experts in measurement and evaluation department to ensure content validity. The reliability of 0.88 at Cronbach alpha using test-retest method, there after Pearson Product Moment Correlation (PPMC) was used. Two (2) research questions were raised to guide this study and they were answered using the PPMC. The findings of the study revealed that digital instructions significantly correlate with academic performance of students in HEI (r = .244**, N= 185, P < .05), and also that digital instructions positively correlate with self – directed learning amongst students in HEI (r = .337***, N= 185, P < .05) at 0.05 level of significance. Based on the findings the following recommendations were made, that articulate use of digital resources ought to be underpinned by deployment of meaningful instructional materials and digital tools and activities. Teachers’ professional competence on the use of digital resources.